SWOT ANALYSIS OF THE HEALTH AND TOURIST CENTER RAJSKA BANJA - POSSIBILITIES OF TOURISM DEVELOPMENT (Heritage, 2022)
People have traveled for a long time to various destinations to use medical services that in the period of health tourism were related to disease prevention, rehabilitation, but also treatment with the help of natural factors. In the second half of the 20th and the beginning of the 21st century, health tourism went beyond the initial framework through a qualitative and quantitative change in the tourist offer. Health tourism implies a temporary change of place of permanent residence for the purpose of health prevention, rehabilitation, use of wellness treatments, as well as the most complex medical procedures. An important resource basis for health tourism is the spa places where appropriate health resorts have been built. The Republic of Serbia is known for its very rich and diverse offer of spa destinations. The study, without the intention to determine a standardized definition of the term, presents various aspects of health tourism and a brief analysis of the development of spa tourism in Serbia. The subject of this paper is the SWOT analysis of the health and tourism center Rajska Banja, with an emphasis on the possibilities of tourism development in the municipality of Zvecan. The aim of the paper is to point out through the valorization of the spa potential in Kosovo and Metohija that health tourism in this area needs a new development concept in accordance with modern trends in the tourist market, in the function of strengthening the tourist offer.
Keywords: health tourism, medical tourism, spa tourism, wellness, SWOT analysis